Challenges in chronic pelvic pain: Diffuse uterine capillary haemangioma simulating a clinical picture of adenomyosis. Issue 4 (December 2021) - Jimenez, Jose Carlos Vilches; Garcia, Ignacio Brunel; Zambrano, Ana Mercedes Betancourt; Ramirez, Vanesa Moreno; Fernandez, Rodrigo Orozco; Sanchez, Manuel Lozano
Introduction: Adenomyosis is a heterogeneous condition of difficult diagnosis that stands out in our patients for causing abundant menstrual bleeding, dyspareunia and dysmenorrhoea. However, in chronic pelvic pain units it is important to consider other conditions of similar symptomatologies, such as vascular malformations. These include capillary haemangiomas which, although rare in the reproductive tract, can produce serious symptoms. Case description: We present the case of a 31-year-old woman under observation by the chronic pelvic pain unit for dysmenorrhoea and dyspareunia since menarche. Ultrasound and magnetic resonance findings were compatible with adenomyosis. The patient showed no improvement with hormonal treatment. Upon failure of the medical treatment and taking into account the patient's lack of gestational desire, a laparoscopic hysterectomy was performed. The pathological report revealed a diffuse capillary haemangioma as the cause of the symptoms. Given the completely curative nature of surgery for this type of condition, the patient was discharged from our unit. Conclusion: The preoperative diagnosis of adenomyosis is still a challenge and units specializing in chronic pelvic pain must consider all possible diagnostic options so as not to overlook rarer conditions such as vascular malformations.